Collaborating with a social housing provider supports a large cohort study of the health effects of housing conditions - Michael G. Baker; Jane Zhang; Tony Blakely; Julian Crane; Kay Saville-Smith; Philippa Howden-Chapman (BMC, 2016)
Abstract Background Despite the importance of adequate, un-crowded housing as a prerequisite for good health, few large cohort studies have explored the health effects of housing conditions. The Social Housing Outcomes Worth (SHOW) Study was established to assess the relationship between housing conditions and health, particularly between household crowding and infectious diseases. This paper reports on the methods and feasibility of using a large administrative housing database for epidemiological research and the characteristics of the social housing population. Methods This prospective open cohort study was established in 2003 in collaboration with Housing New Zealand Corporation which provides housing for approximately 5 % of the population. The Study measures health outcomes using linked anonymised hospitalisation and mortality records provided by the New Zealand Ministry of Health. Results It was possible to match the majority (96 %) of applicant and tenant household members with their National Health Index (NHI) number allowing linkage to anonymised coded data on their hospitalisations and mortality. By December 2011, the study population consisted of 11,196 applicants and 196,612 tenants. Half were less than 21 years of age. About two-thirds identified as Māori or Pacific ethnicity. Household incomes were low. Of tenant households, 44 % containing one or more smokers compared with 33 % for New Zealand as a whole. Exposure to household crowding, as measured by a deficit of one or more bedrooms, was common for applicants (52 %) and tenants (38 %) compared with New Zealanders as whole (10 %). Conclusions This project has shown that an administrative housing database can be used to form a large cohort population and successfully link cohort members to their health records in a way that meets confidentiality and ethical requirements. This study also confirms that social housing tenants are a highly deprived population with relatively low incomes and high levels of exposure to household crowding and environmental tobacco smoke.